Wide-range and selective detection of SARS-CoV-2 DNA via surface modification of electrolyte-gated IGZO thin-film transistors - Hwang, Chuljin; Baek, Seokhyeon; Song, Yoonseok; Lee, Won June; Park, Sungjun (iScience, 2024)
The 2019 coronavirus pandemic resulted in a massive global healthcare crisis, highlighting the necessity to develop effective and reproducible platforms capable of rapidly and accurately detecting SARS-CoV-2. In this study, we developed an electrolyte-gated indium-gallium-zinc-oxide (IGZO) thin-film transistor with sequential surface modification to realize the low limit of detection (LoD <50 fM) and a wide detection range from 50 fM to 5 μM with good linearity (R2 = 0.9965), and recyclability. The surface chemical modification was achieved to anchor the single strand of SARS-CoV-2 DNA via selective hybridization. Moreover, the minute electrical signal change following the chemical modification was investigated by in-depth physicochemical analytical techniques. Finally, we demonstrate fully recyclable biosensors based on oxygen plasma treatment. Owing to its cost-effective fabrication, rapid detection at the single-molecule level, and low detection limit, the proposed biosensor can be used as a point-of-care platform to perform timely and effective SARS-CoV-2 detection.
Keywords: Analytical chemistry; Biomedical materials